Flow resistance analysis of extracranial-to-intracranial (EC–IC) vein bypass - Zhang, Y.; Sia, Sheau Fung; Morgan, M.K.; Qian, Y. (Elsevier, 2012)
Although brain bypass surgery has often been selected to treat internal carotid arteries (ICA) which are restricted by aneurysm or artery stenosis, its effectiveness has not been quantitatively evaluated. The purpose of this study is to propose an innovative approach for the evaluation of brain extracranial-to-intracranial (EC-IC) vein bypass surgery, based on the analysis of flow resistance in vein bypasses and within their contralateral carotid arteries through the use of computational fluid dynamics (CFD). Seven patients who underwent vein bypass surgery were examined with the use of high-resolution; computed tomography angiogram (CTA). The reconstructed three-dimensional (3D) geometries were segmented to create CFD calculation domains. Colour Doppler ultrasound (CDU) was used to measure blood flow velocities at the common carotid arteries (CCA), in order to determine inflow conditions. Based on the pipe flow theory, pressure drop was expressed as Aṁ2+Bṁ where A and B represent flow resistance coefficients and ṁ represents blood mass flow rate. The CFD results revealed that for a healthy ICA, the average values of A and B were 0.013088Pa/(ml/min) 2 and 3.105Pa/(ml/min), respectively. For the vein bypass, an average value of A was 0.0143Pa/(ml/min) 2 and B 3.402Pa/(ml/min), which was approximately that of a healthy ICA. However, in the case of a bypass utilising a venous conduit possessing a large-sized valve or existing size alteration, the flow resistance in that bypass would be higher than those found in the healthy ICA. An imbalance of flow resistances may impose conditions that could predispose hemodynamic failure or distal aneurysm development. © 2012 Elsevier Ltd.